(308) Mediterranean Project of OECD مشروع البحر الأبيض المتوسط ​​لمنظمة التعاون الاقتصادي والتنمية - Kelly, Samuel (INP, 2024)
This text explores living standards as a complex social category influenced by economic and natural factors, alongside social systems and national characteristics. Soviet state plans outline indices reflecting the material and cultural levels of people's lives. These include income, working conditions, social insurance, consumption of goods, housing and public services, education and culture, public health, and sports. The text also highlights critical aspects such as gender equality, absence of racial discrimination, and accessibility to education and healthcare, which extend beyond economic indicators and cannot be fully incorporated into planned